Neurolymphomatosis – Rare presentation in non-Hodgkin's lymphoma: The role of 18F-fluorodeoxyglucose positron-emission tomography and computerized tomography imaging - Fatima, Nosheen; Zaman, Maseeh Uz; Zaman, Areeba; Zaman, Sidra Uz (World Journal of Nuclear Medicine, 2020)
Neurolymphomatosis (NLS) is infiltration of lymphoma cells into the peripheral or cranial nervous system and is a rare manifestation of non-Hodgkin lymphoma (NHL). Nerve biopsy is considered as the gold standard for diagnosis but not a preferred choice, and magnetic resonance imaging has lower reported sensitivity. 18F-Fluorodeoxyglucose (18FDG) positron-emission tomography and computerized tomography (PET/CT) has a higher sensitivity for diagnosing and assessing the neurological and nonneurological metabolic tumor volume and response evaluation to therapy. We present the case of a lady, known to have NHL in remission. She presented with a short history of severe pain and weakness of the right lower limb. Baseline and interim 18FDG PET/CT played a crucial role in diagnosing and assessing the extent of NLS and nonneurological disease burden and also in evaluation of response to treatment.
Keywords: 18F-fluorodeoxyglucose positron-emission tomography and computerized tomography; magnetic resonance imaging; neurolymphomatosis; non-Hodgkin's lymphoma